Impact of Corporate Social Responsibility between Green Accounting and Sustainable Development Goals - Imang Dapit Pamungkas; Muhammad Rafi Raihan; Devina Putri Indra Satata; Anggelica Yufa Kristianto (Universitas Negeri Semarang, 2024)
Purposes: This study aims to test and analyze the impact of CSR on SDGs, Green Accounting's link with SDGs, and CSR's moderating effect on this relationship. Next, it will test and analyze company value as a mediating variable in the relationship between Green Accounting and CSR. Methods: This study uses a quantitative approach. The data included in this study comprises secondary sources, including annual reports and sustainability reports of energy transportation and logistics companies that were listed on the IDX and maintained on corporate websites between 2017 and 2021. This research uses WarpPLS 7.0 software for hypothesis testing and analyzing statistical data. The population of this research is companies that contribute the most significant greenhouse gas emissions in Indonesia. Purposive sampling resulted in a total of 380 samples. Data was collected from annual and sustainability reports from 76 energy, transportation, and logistics companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. Data were processed and analyzed using WarpPLS 7.0 software. Findings: The results of this study show that green accounting has a positive effect on SDGs, and CSR has a significantly positive impact on SDGs. Furthermore, CSR can strengthen the influence of green accounting on the SDGs, and company value can mediate the relationship between green accounting and CSR. Novelty: This research contributes to placing CSR as a moderating variable in the relationship between green accounting and SDGs and placing company value as a mediating variable in the relationship between green accounting and CSR in energy transportation and logistics sector companies in Indonesia.